Incidence, Characteristics, and Management of Patients with Recurrent Myocardial Infarctions: Insights from the EYESHOT POST-MI - Leonardo De Luca; Furio Colivicchi; Domenico Gabrielli; Donata Lucci; Gabriele Grippo; Francesco Piemonte; Bruno Villari; Andrea Di Lenarda; Fabrizio Oliva; Michele Massimo Gulizia (Journal of Interventional Cardiology)
Background. It is unknown whether patients who survived two or multiple episodes of myocardial infarction (MI) present different clinical characteristics and management than patients at their first MI. Methods. The EYESHOT post-MI was a prospective, observational, nationwide study aimed to evaluate the management of patients presenting to cardiologists 1 to 3 years from the last MI event. In 3 months of enrolment, 165 Italian cardiology centers included 1633 consecutive post-MI patients. In the present analysis, we stratified the study cohort according to the number of prior MI episodes (i.e., 1, 2 or ≥3). Results. Among the 1618 patients enrolled with complete data on MI history, 1335 (82.5%) were at their first MI episode, 209 (12.9%) had a history of 2 MIs, and the remaining 74 (4.6%) had ≥ 3 prior MIs. Patients with a history of multiple MIs were increasingly older and presented a significantly higher rate of risk factors compared to those at their first MI. During the year prior to enrolment, patients with 2 or ≥3 MI episodes more frequently underwent coronary angiography compared to the other group (p<0.0001). In addition, several lifesaving and antianginal drugs were more frequently prescribed in patients presenting with a history of multiple MIs compared to those at their first MI. Conclusions. Our data suggest that patients with multiple MIs managed by cardiologists in routine clinical practice present an incremental clinical risk, more frequently undergo coronary angiography, and are more intensively managed with pharmacological therapies compared to patients at their first MI episode.